Prioritizing Disease-Related Microbes Based on the Topological Properties of a Comprehensive Network - Yang, Haixiu; Tong, Fan; Qi, Changlu; Wang, Ping; Li, Jiangyu; Cheng, Liang (Frontiers in Microbiology, 2021)
Many microbes are parasitic within the human body, engaging in various physiological processes and playing an important role in human diseases. The discovery of new microbe–disease associations aids our understanding of disease pathogenesis. Computational methods can be applied in such investigations, thereby avoiding the time–consuming and laborious nature of experimental methods. In this study, we constructed a comprehensive microbe–disease network by integrating known microbe–disease associations from three large–scale databases (Peryton, Disbiome and gutMDisorder), and extended the random walk with restart to the network for prioritizing unknown microbe–disease associations. The area under the curve values of the leave–one–out cross validation and the five–fold cross validation exceeded 0.9370 and 0.9366 respectively, indicating the high performance of this method. Despite being widely studied diseases, in case studies of inflammatory bowel disease, asthma and obesity, some prioritized disease–related microbes were validated by recent literature. This suggested that our method is effective at prioritizing novel disease–related microbes and may offer further insight into disease pathogenesis.